Role of Colonoscopy in Foreign Body (Needle) Ingestion in Children: A Case Report and Literature Review - Harsali F. Lampus; Candy Candy; Leo Rendy; Ronald Sorongku; Sabrandi P. Saputra (Medical Scope Journal, 2024)
Abstract: Foreign body (FB) ingestion is one of the most complex and serious emergency conditions for diagnosis that often occurs in children. Most ingested FBs, intentionally or unintentionally, pass through the gastrointestinal tract without complications, and only a small proportion require surgical intervention inter alia colonoscopy. However, if the patient complains of abdominal pain, complications may occur, especially perforation with peritonitis, and in this case a laparotomy is needed. We reported a case of a 13-year-old girl with the chief complaint of needle ingestion two weeks ago. Patient complained of abdominal pain and was unable to defecate. Plain abdominal radiographs showed needle-shaped metal density in the lower intestinal; therefore, the patient was referred to Prof. Dr. R. D. Kandou Hospital for further treatment. An endoscopy was initially performed but no foreign body was found because they might had been in the intestine. Colonoscopy revealed a foreign body in the proximal ascending colon, transverse position. Extraction of the foreign body, along with pulling the scope and evaluating the transverse, descending, sigmoid and rectum colon which were within normal limits was carried out. Monitoring after removal of the foreign body for two days found no complaints of abdominal pain and bowel movements were normal, therefore, the patient was discharged from the hospital. In conclusion, since a sharp foreign body (a needle) was still in the proximal ascending colon, a colonoscopy was performed with successful removal of the needle. Keywords: foreign body; needle; endoscopy; colonoscopy